Effect of some antiinflammatory plant species on elastase and myeloperoxidase enzyme activity (2012)
In this work, the effect of aqueous and methanolic extracts of the plants species Critoniella acuminata, Salvia rubescens, Phenax rugosus (Poir.) Wedd and Tabebuia chrysanta G. on the enzymes elastase and myeloperoxidase, involved in degranulation leukocyte process, was evaluated, identifying the potential direct inhibitory effect on the enzyme and/or inhibition of the desgranulation of polymorphonuclear neutrophils. Extracts of Critoniella acuminata andSalvia rubescens presented effects on the degranulation process and the inhibition of the enzyme elastase and myeloperoxidase; the extracts of Phenax rugosus do not showed significant effect. Tabebuia chrysanta methanolic extract only showed effect on inhibition of elastase activity.